If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(3x + -6) = 3 + -6x Reorder the terms: 3x + 2(-6 + 3x) = 3 + -6x 3x + (-6 * 2 + 3x * 2) = 3 + -6x 3x + (-12 + 6x) = 3 + -6x Reorder the terms: -12 + 3x + 6x = 3 + -6x Combine like terms: 3x + 6x = 9x -12 + 9x = 3 + -6x Solving -12 + 9x = 3 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -12 + 9x + 6x = 3 + -6x + 6x Combine like terms: 9x + 6x = 15x -12 + 15x = 3 + -6x + 6x Combine like terms: -6x + 6x = 0 -12 + 15x = 3 + 0 -12 + 15x = 3 Add '12' to each side of the equation. -12 + 12 + 15x = 3 + 12 Combine like terms: -12 + 12 = 0 0 + 15x = 3 + 12 15x = 3 + 12 Combine like terms: 3 + 12 = 15 15x = 15 Divide each side by '15'. x = 1 Simplifying x = 1
| x^3-4x^2-x+10=0 | | 7m+2-7m+4= | | 15v^2-19v+6= | | 8x^2+20x+12= | | 16x^2-10xy-6y^2= | | 6x^2-14xy-12y^2= | | 14+3y=-5y-18 | | 20y^2+7y-6= | | 3(-4x-7)=27 | | 3x+7=35-x | | 16y^2+24y-7= | | x^3+8x^2+x-52=0 | | 5y-3x-3=0 | | (20-n)+n+(18-n)=25 | | x+7=42 | | (n+1)+n+(n+1)=25 | | (4x-7)(x+2)=0 | | -2y^2-5y+3= | | -18+3n+n^2=0 | | x^2=4*3 | | 3x^2+15x+56.25=0 | | y=(6x+2)(4x^2+4x+1) | | y=(4x^2+4x+1)(6x+2) | | 4r+3=19r+8 | | 3t+6-4= | | 11=8x+7 | | 40a^2-26ar-30r^2= | | 12q^2-22qd-70d^2= | | 15x^2-31x+14= | | 3y^2+10y+8= | | 3y^2+20y-32= | | 6x^2-53x-9= |